2015
DOI: 10.1016/j.ebcr.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

EEG–EMG polygraphic study of dystonia and myoclonus in a case of Creutzfeldt–Jakob disease

Abstract: We report on a patient with sporadic Creutzfeldt–Jakob disease (CJD) who showed dystonia, periodic myoclonus, and periodic sharp wave complexes (PSWCs) on EEG. The EEG–EMG polygraphic study revealed that dystonia appeared without relation to periodic myoclonus and PSWCs and that dystonia EMGs were strongly suppressed after periodic myoclonus EMGs. These findings suggest that dystonia has a pathogenesis different from that of periodic myoclonus and PSWCs, but dystonia and periodic myoclonus may be generated thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Periodic rhythmic synchronized myoclonus has been suspected due to a hyperexcitable cortico-subcortical loop ( 26 , 27 ). Furthermore, myoclonus occurred more frequently and earlier in MM type at codon 129 of the prion protein gene compared to other codon 129 polymorphism ( 9 , 28 ). This genotype was considered to have the shortest survival compared to MV and VV forms of the human PRNP gene ( 7 , 9 ).…”
Section: Discussionmentioning
confidence: 83%
“…Periodic rhythmic synchronized myoclonus has been suspected due to a hyperexcitable cortico-subcortical loop ( 26 , 27 ). Furthermore, myoclonus occurred more frequently and earlier in MM type at codon 129 of the prion protein gene compared to other codon 129 polymorphism ( 9 , 28 ). This genotype was considered to have the shortest survival compared to MV and VV forms of the human PRNP gene ( 7 , 9 ).…”
Section: Discussionmentioning
confidence: 83%
“…The three cases of the present study were subjected to serial EEG throughout the course of the disease and not all of them had typical PSWC; in the first case, PSWC was not detected, while it rapidly developed in the other two cases at different stages. According to a previous study, EEGs are normal in numerous cases of CJD at the early stage; however abnormal EEG findings may differ among different CJD subtypes (23). Abnormal EEG findings occur in patients with M homozygosis and M/V heterozygosis but rarely in patients with V homozygosis at codon 129 of the PRNP (24).…”
Section: Discussionmentioning
confidence: 99%
“…Hashimoto, T. Iwahashi, W. Ishii, K. Yamamoto, and S.I. Ikeda, [12] evaluated a patient's sporadic Creutzfeldt-Jakob Disease (CJD) who showed dystonia, periodic myoclonus, and Periodic Sharp Wave Complexes (PSWCs) on EEG. The EEG-EMG polygraphic study revealed that dystonia appeared without relation to periodic myoclonus and PSWCs and that dystonia EMGs were strongly suppressed after periodic myoclonus EMGs.…”
Section: Literature Reviewmentioning
confidence: 99%